Criminal Liability Of Perpetrators Of Murder In The Perspective Of Law No. 1 Of 2023 On The Criminal Code (KUHP) - Simanullang, Pio Andina Serepina; Syahranuddin, Syahranuddin; Zarzani, T. Riza (Fakultas Hukum Dehasen, 2026)
The enactment of Law No. 1 of 2023 brings fundamental changes to the Indonesian criminal law landscape, particularly regarding criminal liability for homicide. This study aims to analyze the construction of criminal liability for homicide perpetrators based on Articles 458-462 of the National Criminal Code, and the implications of the new paradigm of sentencing objectives in Articles 51-54. The research method employed is normative juridical with a legislative approach. The study results show that the National Criminal Code emphasizes a balance between legal certainty and restorative justice, where sentencing is no longer merely retributive, but rather an effort toward rehabilitation and conflict resolution.